Increased fruit intake is associated with reduced risk of depression: evidence from cross-sectional and Mendelian randomization analyses - Yan, Zhaoqi; Xu, Yifeng; Li, Keke; Liu, Liangji (Frontiers in Public Health, 2023)
Background The association between dietary patterns and depression has gained significant attention, but the relationship between fruit intake and depression remains unclear. This study aimed to investigate the role of fruit intake in the risk of depression using data from the National Health and Nutrition Examination Survey (NHANES) and Mendelian randomization (MR) analysis, and further explore the causal relationship between them. Materials and methods Cross-sectional analysis was conducted using the 2005–2018 NHANES data. Specialized weighted complex survey design analysis software was used for multivariate logistic analysis. Additionally, genetic variants for fruit intake and depression, as well as its related neuroticism traits, from the GWAS were used as instrumental variables in MR analysis. The inverse variance weighted (IVW) method was employed as the primary analysis method to evaluate the causal relationship between them. MR-Egger regression, MR-PRESSO test, and leave-one-out analysis were conducted to assess heterogeneity and pleiotropy. Results In NHANES, compared to the lowest quartile (Q1, <0.12 cup], the highest quartile (Q4, >1.49 cups) of fruit intake showed a significant reduction in the risk of depression after adjusting for relevant covariates. Model 3, after rigorous adjustment for multiple covariates, demonstrated improved predictive performance in both Receiver operating characteristic (ROC) curve and Decision curve analysis (DCA). In Model 3, the proportion of reduced depression risk associated with fruit intake reached 31% (OR = 0.69, 95% CI: 0.50–0.95). This association remained significant in the MR analysis (OR = 0.92, 95% CI = 0.87–0.96; p = 5.09E-04). Fruit intake was also associated with a decreased risk of neuroticism traits related to depression, including feeling lonely (OR = 0.82, 95% CI = 0.74–0.90; p = 2.91E-05), feeling miserable (OR = 0.79, 95% CI = 0.72–0.87; p = 2.35E-06), feeling fed-up (OR = 0.75, 95% CI = 0.68–0.83; p = 2.78E-08), irritable mood (OR = 0.89, 95% CI = 0.79–0.99; p = 0.03), and neuroticism (OR = 0.85, 95% CI = 0.76–0.96; p = 9.94E-03). The causal relationship between feeling lonely and fruit intake was bidirectional. Conclusion Increased fruit intake has a causal effect in reducing the risk of depression and is beneficial for related psychological well-being.